High-entropy alloy catalyst and preparation method thereof

The deposition of high-entropy alloys with a specific metal ratio on reduced graphene oxide by pulse microwave method solves the problems of uneven particle distribution and unstable catalytic activity in the prior art, and realizes the preparation of high-efficiency and durable low-platinum content high-entropy alloy catalysts, reducing the cost of fuel cells.

CN119890331APending Publication Date: 2025-04-25CROWN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311386256.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare low-platinum content high-entropy alloy catalysts with uniform particle distribution, and it is difficult to maintain catalytic activity and durability.

Method used

A high-entropy alloy catalyst was prepared by pulse microwave method, and a high-entropy alloy containing a specific metal proportion was deposited on reduced graphene oxide, including alloys of metals such as 26.6-32.9 at.% platinum, 11.2-16.6 at.% aluminum, 14.9-20.1 at.% manganese and other metals.

Benefits of technology

The preparation of a low-platinum content high-entropy alloy catalyst with uniform particle distribution is achieved, with excellent catalytic ability and durability, and can effectively replace platinum-based catalysts and reduce the cost of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890331A_ABST
    Figure CN119890331A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy alloy catalyst and a preparation method thereof, the high-entropy alloy catalyst with uniform particle distribution and low platinum content is prepared by using pulse microwaves, and a platinum-based catalyst can be replaced by a high-entropy alloy with excellent catalytic capability and durability. Therefore, the effects of reducing the cost of the fuel cell and keeping the capability of effectively catalyzing the oxidation-reduction reaction can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an alloy catalyst and a preparation method thereof, in particular to a high entropy alloy catalyst with uniform particle distribution and low platinum content and a preparation method thereof. Background Art

[0002] Conventional fuel cells mostly use platinum (Pt)-based catalysts. However, due to the high price and scarcity of platinum, it is not conducive to the widespread application of such platinum-based catalysts. Therefore, it is necessary to study non-platinum-based catalysts or catalysts with low platinum content that have similar catalytic activity and catalytic durability.

[0003] There have been studies on using high-entropy alloys as catalysts in fuel cells. High-entropy alloys are usually new alloys formed by five or more metals in equal or relative proportions, and can be composed of various combinations and structures. However, due to the difficulty in preparing high-entropy alloys, the application of high-entropy alloy catalysts only began a few years ago.

[0004] One method for preparing alloy catalysts is a continuous microwave heating method, which uses continuous microwaves to deposit metals (e.g., Pt-M (M = Co, Sn, Zn)) on various carbon supports (e.g., such as carbon black (XC-72), carbon nanotubes and graphene oxide (GO)) to prepare alloy catalysts. However, the continuous microwave heating method cannot control and separate the nucleation and growth steps, which will cause the problem of uneven particle distribution. Therefore, how to prepare alloy catalysts with uniform particle distribution and maintain or improve the catalytic activity and catalytic stability of the alloy catalyst while reducing the platinum content is an important issue. Summary of the invention

[0005] The present invention provides a high entropy alloy catalyst and a preparation method thereof. A high entropy alloy with uniform particle distribution and low platinum content is prepared by using pulse microwaves. The high entropy alloy with excellent catalytic ability and durability can replace the platinum-based catalyst, thereby reducing the cost of the fuel cell and maintaining the ability to effectively catalyze redox reactions.

[0006] In order to achieve the above-mentioned object, the present invention provides a high entropy alloy catalyst, comprising: a carrier, comprising reduced graphene oxide (rGO); and a high entropy alloy, located on the reduced graphene oxide; wherein the high entropy alloy comprises 26.6 atomic percent (at.%) to 32.9 at.% platinum, 11.2 at.% to 16.6 at.% aluminum, 14.9 at.% to 20.1 at.% manganese, 3.8 at.% to 9.1 at.% cobalt, 15.6 at.% to 21.5 at.% nickel, 0 at.% to 15.9 at.% iron and 0 at.% to 16.8 at.% copper, and the iron and copper are not 0 at.% at the same time.

[0007] In addition, the present invention also provides a method for preparing a high entropy alloy catalyst, comprising: adding a solution containing multiple metal ions into an alkaline solution, and then adding ethylene glycol, wherein the multiple metal ions include platinum ions, aluminum ions, manganese ions, cobalt ions and nickel ions, and the multiple metal ions further include iron ions and / or copper ions; dispersing graphene oxide in the alkaline solution to obtain a solution; placing the solution in an ultrasonic water bath for ultrasonic oscillation to prepare a homogeneous slurry; subjecting the homogeneous slurry to pulse microwave radiation for a deposition reaction; centrifuging the homogeneous slurry after the reaction is completed to separate a crude product; washing the crude product with deionized water several times and drying the crude product to obtain a high entropy alloy catalyst.

[0008] The high entropy alloy catalyst and preparation method provided by the present invention utilize pulse microwave to prepare a high entropy alloy with uniform particle distribution and low platinum content, and can achieve the effect of reducing the cost of fuel cells while maintaining the ability to effectively catalyze redox reactions by replacing platinum-based catalysts with high entropy alloys with excellent catalytic ability and catalytic durability.

[0009] The above description of the content of the present invention and the following description of the embodiments are for illustrating and explaining the spirit and principle of the present invention, and provide further explanation for the scope of the patent application of the present invention. However, it is obvious to those skilled in the art that these examples are only for illustrating the present invention and should not be construed as limiting the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The above and other objects, features and other advantages of the present invention will be more particularly explained by the following detailed description in conjunction with the accompanying drawings.

[0011] Figure 1 Field emission scanning electron microscope (FE-SEM) images of graphene oxide, a comparative example, and a high entropy alloy catalyst according to the first embodiment and the second embodiment of the present invention.

[0012] FIG. 2A to FIG. 2CThe cyclic voltammograms of the high entropy alloy catalysts according to the comparative example, the first embodiment and the second embodiment of the present invention at different scan rates are shown respectively.

[0013] FIG. 3A to FIG. 3C The cyclic voltammograms of the high entropy alloy catalysts according to the comparative example, the first embodiment and the second embodiment of the present invention are shown respectively.

[0014] FIG. 4A to FIG. 4C 1 and 10 are linear voltammograms of the high entropy alloy catalysts according to the comparative example, the first embodiment and the second embodiment of the present invention.

[0015] Figure 5 This is the equivalent circuit configured for measuring internal resistance.

[0016] FIG. 6A to FIG. 6C Impedance diagrams of high entropy alloy catalysts according to a comparative example, the first embodiment and the second embodiment of the present invention, respectively. DETAILED DESCRIPTION

[0017] The advantages and features of the present invention and the methods for achieving the advantages and features will become clear by detailed reference to the following exemplary embodiments and drawings. However, the present invention is not limited to the exemplary embodiments in this application and can be implemented in various different forms. The exemplary embodiments are provided only by way of example so that those of ordinary skill in the art to which the present invention belongs can fully understand the present invention and the scope of the present invention.

[0018] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values ​​(including integers and decimals) within the range. For example, the range description of "1.00 to 8.00", "1.00-8.00", "between 1.00 and 8.00" or "between 1.00 and 8.00" should be deemed to have specifically disclosed all secondary ranges such as 1.00 to 8.00, 1.00 to 7.00, 2.00 to 8.00, 2.00 to 6.00, 3.00 to 6.00, 4.00 to 8.00, 3.00 to 8.00, and includes endpoint values.

[0019] The high entropy alloy catalyst and the preparation method thereof of the present invention will be described in detail below with reference to the accompanying drawings.

[0020] According to an embodiment of the present invention, a high entropy alloy catalyst comprises: a carrier comprising reduced graphene oxide; and a high entropy alloy located on the reduced graphene oxide; wherein the high entropy alloy comprises 26.6at.% to 32.9at.% platinum, 11.2at.% to 16.6at.% aluminum, 14.9at.% to 20.1at.% manganese, 3.8at.% to 9.1at.% cobalt, 15.6at.% to 21.5at.% nickel, 0at.% to 15.9at.% iron and 0at.% to 16.8at.% copper, and iron and copper are not 0at.% at the same time, but are not limited thereto. The carrier may also be a carbon carrier such as carbon black and carbon nanotubes as appropriate. The high entropy alloy may also be a high entropy alloy composed of other proportions of the above metals or other metals as appropriate. Iron and copper in the high entropy alloy of the present invention may exist at the same time, but cannot be free of iron and copper at the same time, preferably only copper or only iron.

[0021] In another embodiment of the present invention, the high entropy alloy may include 26.6at.% to 31.6at.% platinum, 11.2at.% to 16.2at.% aluminum, 15.1at.% to 20.1at.% manganese, 3.8at.% to 8.8at.% cobalt, 16.5at.% to 21.5at.% nickel, 10.9at.% to 15.9at.% iron and 0at.% copper. In another embodiment of the present invention, the high entropy alloy may include 29.1at.% platinum, 13.7at.% aluminum, 17.6at.% manganese, 6.3at.% cobalt, 19.0at.% nickel, 13.4at.% iron and 0at.% copper. In another embodiment of the present invention, the average particle size of the high entropy alloy may be 2.41nm.

[0022] In another embodiment of the present invention, the high entropy alloy may include 27.9at.% to 32.9at.% platinum, 11.6at.% to 16.6at.% aluminum, 14.9at.% to 19.9at.% manganese, 4.1at.% to 9.1at.% cobalt, 15.6at.% to 20.6at.% nickel, 0at.% iron and 11.8at.% to 16.8at.% copper. In another embodiment of the present invention, the high entropy alloy may include 30.4at.% platinum, 14.1at.% aluminum, 17.4at.% manganese, 6.6at.% cobalt, 18.1at.% nickel, 0at.% iron and 14.3at.% copper. In another embodiment, the average particle size of the high entropy alloy may be 2.35nm.

[0023] The high entropy alloy of the present invention has excellent catalytic effect and catalytic durability, and can be used to replace platinum-based catalysts, thereby achieving the effect of reducing the cost of fuel cells and maintaining the ability to effectively catalyze redox reactions.

[0024] According to an embodiment of the present invention, a method for preparing a high entropy alloy catalyst comprises: adding a solution containing a plurality of metal ions to an alkaline solution, and then adding ethylene glycol, wherein the plurality of metal ions include platinum ions, aluminum ions, manganese ions, cobalt ions and nickel ions, and the plurality of metal ions further include iron ions and / or copper ions, and wherein the alkaline solution can be prepared by potassium hydroxide (KOH). Graphene oxide is dispersed in the alkaline solution to obtain a solution; the solution is placed in an ultrasonic water bath for ultrasonic oscillation for 30 minutes to prepare a homogeneous slurry; the homogeneous slurry is subjected to pulse microwave radiation for deposition reaction; the reaction-completed solution is centrifuged to separate a crude product; the crude product is washed with deionized water several times and the crude product is placed in an oven to dry to obtain a high entropy alloy catalyst. The preparation method of the high entropy alloy catalyst of the present invention can achieve the effect of preparing a high entropy alloy catalyst with uniform particle distribution.

[0025] The solution capable of providing platinum ions used in the present invention can be other solutions known to those of ordinary skill in the art that can provide platinum ions and will not react with aluminum ions, manganese ions, cobalt ions, nickel ions, copper ions, and iron ions, such as precipitation reactions. Thus, the present invention uses a platinum tetrachloride aqueous solution, but is not limited thereto.

[0026] The solution capable of providing aluminum ions used in the present invention can be other solutions known to those skilled in the art that can provide aluminum ions and will not react with platinum ions, manganese ions, cobalt ions, nickel ions, copper ions, and iron ions, such as precipitation reactions. Thus, the present invention uses an aqueous solution of aluminum nitrate, but is not limited thereto.

[0027] The solution capable of providing manganese ions used in the present invention can be other solutions known to those skilled in the art that can provide manganese ions and will not react with platinum ions, aluminum ions, cobalt ions, nickel ions, copper ions, and iron ions, such as precipitation reactions. Thus, the present invention uses an aqueous solution of manganese nitrate, but is not limited thereto.

[0028] The solution capable of providing cobalt ions used in the present invention can be other solutions known to those skilled in the art that can provide cobalt ions and will not react with platinum ions, aluminum ions, manganese ions, nickel ions, copper ions, and iron ions, such as precipitation reactions. Thus, the present invention uses an aqueous solution of cobalt nitrate, but is not limited thereto.

[0029] The solution capable of providing nickel ions used in the present invention can be other solutions known to those skilled in the art that can provide nickel ions and will not react with platinum ions, aluminum ions, manganese ions, cobalt ions, copper ions, and iron ions, such as precipitation reactions. Thus, the present invention uses a nickel nitrate aqueous solution, but is not limited thereto.

[0030] The solution capable of providing iron ions used in the present invention can be other solutions known to those skilled in the art that can provide iron ions and will not react with platinum ions, aluminum ions, manganese ions, cobalt ions, nickel ions, and copper ions, such as precipitation reactions. Thus, the present invention uses an aqueous solution of ferric nitrate, but is not limited thereto.

[0031] The solution capable of providing copper ions used in the present invention can be other solutions known to those skilled in the art that can provide copper ions and will not react with platinum ions, aluminum ions, manganese ions, cobalt ions, nickel ions, and iron ions, such as precipitation reactions. Thus, the present invention uses a copper nitrate aqueous solution, but is not limited thereto.

[0032] The preparation, testing and test results of high entropy alloy catalysts according to various embodiments of the present invention are described below.

[0033] Preparation Example

[0034] 1. Preparation of the first example (Fe-HEA-GO)

[0035] Preparation steps: Precursors (platinum tetrachloride (PtCl4), aluminum nitrate nonahydrate (Al(NO3)3·9H2O), manganese nitrate tetrahydrate (Mn(NO3)2·4H2O), cobalt nitrate hexahydrate (Co(NO3)2·6H2O), nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and iron nitrate nonahydrate (Fe(NO3)3·9H2O)) were dissolved in 50 milliliters (mL) of deionized water to obtain a precursor solution with a volume molar concentration (M) of 0.04. 2 mL of the above 0.04 M precursor solution was gradually added to 10 mL of an alkaline solution under continuous stirring mode, and the alkaline solution was adjusted to a solution with a pH value of 11.7 by a 0.04 M potassium hydroxide (KOH) solution, followed by the addition of 30 mL of ethylene glycol (EG). Then 200 milligrams (mg) of graphene oxide were dispersed in the above alkaline solution containing various metal ions. Next, the solution in the above step is placed in an ultrasonic water bath for ultrasonic oscillation for 30 minutes to prepare a homogeneous slurry. A pulsed microwave reactor is used to irradiate the homogeneous slurry subjected to ultrasonic oscillation for 10 minutes (120 cycles of pulsed microwaves with an opening time of 3 seconds and a closing time of 2 seconds) with a power of 700 watts (W) and a frequency of 2.45 gigahertz (GHz) to provide energy for metal ion reduction, while a K-type thermocouple is used to control the maximum temperature to 100°C to ensure that the high entropy alloy is deposited on graphene oxide. After the deposition reaction is completed, the crude product of the high entropy alloy catalyst is separated by centrifugation. Finally, the crude product centrifuged is washed several times with deionized water and the crude product is placed in an 80°C oven for drying for 1 hour to remove the remaining moisture, thereby obtaining a high entropy alloy catalyst. 25 mg of catalyst, 300 μL of Nafion film and 3 mL of 2-propanol were added to a sample bottle, and the sample bottle was placed in an ultrasonic water bath for ultrasonic vibration for 30 minutes. The sample in the vibrated sample bottle was then dropped onto carbon paper using a drop coating method for subsequent application.

[0036] 2. Preparation of the Second Example (Cu-HEA-GO)

[0037] Preparation steps: Except for replacing the iron nitrate nonahydrate (Fe(NO3)3·9H2O) prepared in the first embodiment with copper nitrate trihydrate (Cu(NO3)2·3H2O), the remaining preparation steps are the same as those of the first embodiment.

[0038] 3. Preparation of Comparative Example (Pt-GO)

[0039] Preparation steps: Except for changing the precursor prepared in the first embodiment to use only platinum tetrachloride (PtCl4), the remaining preparation steps are the same as those of the first embodiment.

[0040] Analysis of physical and chemical properties of catalysts

[0041] Experiment 1: The ratio of each metal element in each catalyst was analyzed by energy-dispersive X-ray spectroscopy (EDS), and the results are shown in Table 1. The atomic percentage (at.%) is the ratio of the number of atoms of a certain metal element in the high entropy alloy catalyst to the number of atoms of all metal elements in the high entropy alloy catalyst.

[0042] Table 1

[0043]

[0044]

[0045] Experiment 2: The structural properties of the high entropy alloy catalysts of each catalyst were measured by X-ray diffractometer (XRD). The results are shown in Table 2.

[0046] Table 2

[0047] Comparative Example First embodiment Second embodiment <![CDATA[d XRD (nm)]]> 4.70 2.41 2.35 <![CDATA[d (111) (nm)]]> 0.225 <![CDATA[0.226 # / 0.224 * ]]> 0.224 <![CDATA[L a (nm)]]> 0.390 <![CDATA[0.391 # / 0.388 * ]]> 0.389 deviation(%) 0.240 <![CDATA[0 # / 0.716 * ]]> 0.478

[0048] #: first peak; *: second peak

[0049] It can be seen from Table 2 that the average particle sizes of the high entropy alloy catalysts of the first embodiment and the second embodiment are 2.41nm and 2.35nm, respectively, which are both smaller than the comparative example (4.7nm). When measuring the (111) crystal plane spacing of the high entropy alloy catalyst of the first embodiment, two peaks were measured, which were 0.226nm and 0.224nm, respectively, while the (111) crystal plane spacing of the high entropy alloy catalyst of the second embodiment was 0.224nm. When measuring the lattice constant of the high entropy alloy catalyst of the first embodiment, two peaks were measured, which were 0.391nm and 0.388nm, respectively, while the lattice constant of the high entropy alloy catalyst of the second embodiment was 0.389nm.

[0050] Experiment 3: Observation of the surface of each sample using a field emission scanning electron microscope (FE-SEM)

[0051] Field emission scanning electron microscopy was used to observe the graphene oxide without deposition reaction, the high entropy alloy catalyst of the first embodiment, the second embodiment and the comparative example. Figure 1 As shown, Figure 1(a) to (d) are field emission scanning electron microscope photos of graphene oxide, comparative example, first embodiment, and second embodiment, respectively. Figure 1 It can be seen that compared with the graphene oxide without alloy or metal deposition, Figure 1 (a) Figure 1 (b) Figure 1 (c) Figure 1 The metal particles (white dots) of the comparative example, the first embodiment, and the second embodiment of (d) are indeed deposited on the graphene oxide and are evenly distributed.

[0052] Experiment 4: Observation of the electrochemical characteristics of each catalyst by cyclic voltammetry (CV)

[0053] (1) Observe the potential-current relationship of each catalyst by cyclic voltammetry at different scan rates

[0054] The comparative example, the first embodiment and the second embodiment were placed in a 1.0 M sulfuric acid solution under a nitrogen environment, and the current sizes of the comparative example, the first embodiment and the second embodiment in the potential range of -0.2 volts (V) to 0.8 V (vsAg / AgCl) were measured at scan rates of 10 mV / s, 30 mV / s, 50 mV / s, 70 mV / s and 100 mV / s (mV / s), respectively.

[0055] The results are shown in Figure 2. FIG. 2A to FIG. 2C The cyclic voltammograms of the high entropy alloy catalysts at different scanning rates are respectively a comparative example, the first embodiment according to the present invention, and the second embodiment. Figure 2B and Figure 2C It can be seen that the peak shift phenomenon of hydrogen adsorption and desorption between -0.2V and 0.2V of the high entropy alloy catalysts of the first and second embodiments at different scanning rates is not obvious, indicating that the high entropy alloy catalyst particles of the first and second embodiments are small and have low impedance.

[0056] (2) Cyclic voltammetry was used to test the catalytic activity of each catalyst after 50 cycles and 500 cycles.

[0057] The comparative example, the first embodiment and the second embodiment were placed in a 1.0 M sulfuric acid solution under a nitrogen environment, and the current of the comparative example, the first embodiment and the second embodiment was measured at a scanning rate of 70 mV / s when 50 cycles and 500 cycles were performed in the potential range of -0.2 volts (V) to 0.8 V (vsAg / AgCl).

[0058] The test results are shown in Figure 3. FIG. 3A to FIG. 3C The cyclic voltammograms of the high entropy alloy catalysts according to the comparative example, the first embodiment and the second embodiment of the present invention are shown respectively. Figure 3B and Figure 3CIt can be seen that the potential-current curves of the high entropy alloy catalysts of Example 1 and Example 2 after 50 and 500 cycles are similar, indicating that the high entropy alloy catalysts of Example 1 and Example 2 can also have similar catalytic performance after 500 cycles, and have excellent catalytic stability and catalytic durability.

[0059] Experiment 5: Observation of the catalytic activity of each catalyst by linear sweep voltammetry (LSV)

[0060] The comparative example, the first embodiment and the second embodiment were placed in a 0.1M potassium hydroxide (KOH) solution in an oxygen environment, and the current of the comparative example, the first embodiment and the second embodiment was measured at a scanning rate of 50mV / s in the potential range of -0.8V to 0.8V (vsAg / AgCl).

[0061] The test results are as follows FIG. 4A to FIG. 4C As shown, FIG. 4A to FIG. 4C They are the linear sweep voltammograms of the comparative example, the first embodiment, the second embodiment, the linear sweep voltammogram during the oxygen evolution reaction (OER), and the linear sweep voltammogram during the oxygen reduction reaction (ORR). Figure 4B It can be seen that the catalytic ability of the high entropy alloy catalysts of the first embodiment and the second embodiment for oxygen evolution reaction is better than that of the comparative example, and Figure 4C It can be seen that the catalytic ability of the high entropy alloy catalysts of the first and second embodiments for oxygen reduction reaction is superior to that of the comparative example.

[0062] Test 6: Measuring the internal resistance of each catalyst

[0063] by Figure 5 The apparatus of this test was configured according to the equivalent circuit diagram, and the internal resistance of the high entropy alloy catalysts of the comparative example, the first embodiment, and the second embodiment before and after 500 cycles was measured.

[0064] The test results are as follows FIG. 6A to FIG. 6C As shown, FIG. 6A to FIG. 6C The impedance diagrams of the high entropy alloy catalysts according to the comparative example, the first embodiment and the second embodiment of the present invention are shown respectively. FIG. 6A to FIG. 6C It can be seen that the internal resistance of the high entropy alloy catalysts of Examples 1 and 2 is smaller than that of the comparative example, which is conducive to application in batteries, and even after 500 cycles, the internal resistance of the high entropy alloy catalysts of Examples 1 and 2 is smaller than that of the comparative example.

[0065] In summary, the high entropy alloy catalyst and preparation method thereof provided by the present invention can utilize pulsed microwaves to prepare a high entropy alloy catalyst with a low platinum content and uniform particle distribution, and can replace the platinum-based catalyst with a high entropy alloy catalyst with excellent catalytic ability and catalytic durability, thereby achieving the effect of reducing the cost of the fuel cell and maintaining the ability to effectively catalyze redox reactions.

Claims

1. A high entropy alloy catalyst comprising: a support comprising reduced graphene oxide; and A high entropy alloy is disposed on the carrier; in, The high entropy alloy includes 26.6 atomic percent (at.%) to 32.9 at.% platinum, 11.2 at.% to 16.6 at.% aluminum, 14.9 at.% to 20.1 at.% manganese, 3.8 at.% to 9.1 at.% cobalt, 15.6 at.% to 21.5 at.% nickel, 0 at.% to 15.9 at.% iron and 0 at.% to 16.8 at.% copper, and iron and copper are not 0 at.% at the same time.

2. The high entropy alloy catalyst according to claim 1, wherein The high entropy alloy comprises 26.6 at.% to 31.6 at.% platinum, 11.2 at.% to 16.2 at.% aluminum, 15.1 at.% to 20.1 at.% manganese, 3.8 at.% to 8.8 at.% cobalt, 16.5 at.% to 21.5 at.% nickel, 10.9 at.% to 15.9 at.% iron and 0 at.% copper.

3. The high entropy alloy catalyst according to claim 2, wherein: The high entropy alloy includes 29.1 at.% platinum, 13.7 at.% aluminum, 17.6 at.% manganese, 6.3 at.% cobalt, 19.0 at.% nickel, 13.4 at.% iron and 0 at.% copper.

4. The high entropy alloy catalyst according to claim 2 or 3, wherein: The average particle size of the high entropy alloy is 2.41 nm.

5. The high entropy alloy catalyst according to claim 1, wherein The high entropy alloy comprises 27.9 at.% to 32.9 at.% platinum, 11.6 at.% to 16.6 at.% aluminum, 14.9 at.% to 19.9 at.% manganese, 4.1 at.% to 9.1 at.% cobalt, 15.6 at.% to 20.6 at.% nickel, 0 at.% iron and 11.8 at.% to 16.8 at.% copper.

6. The high entropy alloy catalyst according to claim 5, wherein The high entropy alloy includes 30.4 at.% platinum, 14.1 at.% aluminum, 17.4 at.% manganese, 6.6 at.% cobalt, 18.1 at.% nickel, 0 at.% iron and 14.3 at.% copper.

7. The high entropy alloy catalyst according to claim 7, wherein: The average particle size of the high entropy alloy is 2.35 nm.

8. A method for preparing a high entropy alloy catalyst according to any one of claims 1 to 7, comprising: Adding a solution containing a plurality of metal ions to an alkaline solution, followed by adding ethylene glycol, wherein the plurality of metal ions comprises platinum ions, aluminum ions, manganese ions, cobalt ions and nickel ions, and the plurality of metal ions further comprises iron ions and / or copper ions; dispersing graphene oxide in the alkaline solution to obtain a solution; placing the solution in an ultrasonic water bath for ultrasonic oscillation to prepare a homogeneous slurry; subjecting the homogeneous slurry to pulse microwave radiation to perform a deposition reaction; Centrifuging the homogeneous slurry after the reaction is completed to separate the crude product; The crude product was washed several times with deionized water and dried to obtain a high entropy alloy catalyst.